The Missiles of October - Devane, William 1937-; Sheen, Martin 1940-; Da Silva, Howard 1909-1986; Page, Anthony 1935-; Brodkin, Herbert; Greenberg, Stanley R. 1927-2002 (MPI Home Video, 2004)
A dramatic reenactment of the events surrounding the Cuban missile crisis of October 16, 1962, when President John F. Kennedy of the United States forced the Soviet Union to remove its missiles from Cuba